2020
DOI: 10.1590/0001-3765202020200691
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise during coronavirus disease (COVID-19): Recommendations to remaining active in periods of confinement

Abstract: The period of social isolation during the COVID-19 pandemic has led people to adopt behaviors that were not previously part of their routines. The need to maintain an active lifestyle, with the adoption of an exercise regimen, has been reinforced by the scientifi c community for the maintenance of the immune and mental condition. Thus, we point out the need to observe the scientifi c guidelines on physical exercises during social isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Up to now, no study has illustrated the straight effects of physical activity on patients with COVID-19. In general, all researches have considered the in luences of physical activity on reducing the risks of COVID-19 [1,[17][18][19][20]. Studies, before the occurrence of the COVID-19 pandemic, had examined the relationship between exercising and the immune system function [21,22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, no study has illustrated the straight effects of physical activity on patients with COVID-19. In general, all researches have considered the in luences of physical activity on reducing the risks of COVID-19 [1,[17][18][19][20]. Studies, before the occurrence of the COVID-19 pandemic, had examined the relationship between exercising and the immune system function [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have examined the acute effects of an exercise bout on the immune system of the elderly, and the results showed that even one session could improve immune response [25]. However, studies on athletes and their immune system responses in short-term and longterm training demonstrated that the immune system is enhanced by regular exercise, suggesting that athletes may be more resistant to the coronavirus than others [17]. On the other hand, little information is available on the longterm effects of training on the immune system of the elderly https://doi.org/10.29328/journal.jsmt.1001051 [26].…”
Section: Physiological Eff Ects Of Physical Activity During the Covidmentioning
confidence: 99%
“…De modo geral, os estudos selecionados sugerem que a forma e o ambiente da atividade física e exercício físico sejam adaptados ao contexto em que se está inserido o indivíduo, incluindo atividades seguras ao ar livre [24][25][28][29]31,35,42 e no ambiente domiciliar 25,[30][31]42 . Foi aconselhada diminuição do comportamento sedentário residencial, com atividades básicas e instrumentais da vida diária [24][25]40 , mediante gasto energético demandado.…”
Section: Discussionunclassified
“…The COVID-19 pandemic beginning in 2020 changed how we live and relate to each other during and after lockdown/confinement. That situation produced studies linked to questions such as a possible reduction in physical exercise [10], the psychological effects of confinement [11,12], changes in patterns of alcohol consumption [13], problematic internet use [12], and changes in the use of technological devices [14].…”
Section: Introductionmentioning
confidence: 99%